Validation of In utero Tractography of Human Fetal Commissural and Internal Capsule Fibers with Histological Structure Tensor Analysis - Mitter, Christian; Jakab, András; Brugger, Peter C.; Ricken, Gerda; Gruber, Gerlinde M.; Bettelheim, Dieter; Scharrer, Anke; Langs, Georg; Hainfellner, Johannes A.; Prayer, Daniela; Kasprian, Gregor (Frontiers in Neuroanatomy, 2015)
Diffusion tensor imaging (DTI) and tractography offer the unique possibility to visualize the developing white matter macroanatomy of the human fetal brain in vivo and in utero and are currently under investigation for their potential use in the diagnosis of developmental pathologies of the human central nervous system. However, in order to establish in utero DTI as a clinical imaging tool, an independent comparison between macroscopic imaging and microscopic histology data in the same subject is needed. The present study aimed to cross-validate normal as well as abnormal in utero tractography results of commissural and internal capsule fibers in human fetal brains using postmortem histological structure tensor (ST) analysis. In utero tractography findings from two structurally unremarkable and five abnormal fetal brains were compared to the results of postmortem ST analysis applied to digitalized whole hemisphere sections of the same subjects. An approach to perform ST-based deterministic tractography in histological sections was implemented to overcome limitations in correlating in utero tractography to postmortem histology data. ST analysis and histology-based tractography of fetal brain sections enabled the direct assessment of the anisotropic organization and main fiber orientation of fetal telencephalic layers on a micro- and macroscopic scale, and validated in utero tractography results of corpus callosum and internal capsule fiber tracts. Cross-validation of abnormal in utero tractography results could be achieved in four subjects with agenesis of the corpus callosum and in two cases with malformations of internal capsule fibers. In addition, potential limitations of current DTI-based in utero tractography could be demonstrated in several brain regions. Combining the three-dimensional nature of DTI-based in utero tractography with the microscopic resolution provided by histological ST analysis may ultimately facilitate a more complete morphologic characterization of axon guidance disorders at prenatal stages of human brain development.